The effect of Information and Communication Technology and Procurement towards Supply Chain Integration (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Supply chain integration is widely considered by both practitioners and researchers a vital contributor to supplychain performance. The two key flows in such relationships are procurement and information technology. Previous studieshave addressed information technology and procurement in separate studies. In this paper, we investigate the integrations ofboth information communication technology and procurement between supply chain partners and their effect on supply chainintegration. Information technology capabilities and procurement both have significant effects on supply chain integration.This concept paper will discuss the importance of information and communication technology and also procurement in order tosurvive and sustain a competitive, which in turn to improve supply chain integration. Additionally, the proposed frameworkwill be useful in any environment as it resulted from the synthesis of past literatures and studies. This study is one of the first toidentify and discuss conceptually the relationship between information technology, procurement and supply chain integration.